The Implementation of Interactive Learning Through ICT in English Language Education for Junior High School Students - Alvina Damayanti; Dzul Rachman; Yeni Rahmawati (English Language Education Department, Universitas Majalengka, 2025)
This study investigates the implementation of interactive learning through Information and Communication Technology (ICT) in English language education for junior high school students. Employing a mixed-methods approach, the research aims to explore how ICT is applied in English classrooms, the challenges faced by teachers and students, and its effectiveness in enhancing students’ understanding and motivation. Data were gathered through interviews with English teachers and questionnaires completed by students. The findings reveal that teachers use various digital platforms such as Quizizz, Padlet, YouTube, and Word wall to create engaging and interactive learning environments. These tools are effective in increasing students’ participation, improving comprehension, and supporting vocabulary acquisition. Students responded positively, indicating that ICT-based learning made lessons more enjoyable and easier to follow. However, several challenges were identified, including classroom management difficulties and the need for continuous teacher training in digital pedagogy. The study concludes that while ICT integration offers substantial benefits in motivating students and improving learning outcomes, its success relies on teachers’ digital competence and institutional support. The results highlight the need for strategic implementation, regular professional development, and appropriate infrastructure to ensure sustainable and effective use of ICT in English language education.